ANALYSIS OF ADVANCED GASTRIC CANCER IN THE REPUBLIC OF BASHKORTOSTAN FOR A MULTIYEAR PERIOD OBSERVATIONS - I. R. Rakhmatullina; D. T. Arybzhanov; A. M. Khanov; G. Kh. Akhmadullina (Креативная хирургия и онкология)
The article analyzed  the  incidence  of gastric  cancer  in the  Republic of Bashkortostan from  1993 to  2002  and  from  2003  to  2012. A comparative analysis  of  cancer  incidence rates  of primary tumors of the stomach, obtained regularities level dynamics  of disease  in different years, depending on age and gender.